Mesoscale Structures in Earth's Magnetotail Observed Using Energetic Neutral Atom Imaging. Issue 3 (4th February 2021) - Keesee, A. M.; Buzulukova, N.; Mouikis, C.; Scime, E. E.
Abstract: Mesoscale structures in Earth's magnetotail are a primary feature of particle transport to the inner magnetosphere during storms and substorms. We demonstrate that such structures can be observed in energetic neutral atom (ENA) data which can provide remote, global images of the magnetosphere. In particular, we present localized regions of increased ion temperatures that appear in equatorial ion temperature maps calculated from Two Wide‐angle Imaging Neutral‐atom Spectrometers (TWINS) ENA data. These regions are associated with a dipolarization front with bursty ion flows measured by Magnetospheric MultiScale (MMS) and are concurrent with substorm features observed in field aligned currents (FAC) from Active Magnetosphere and Planetary Electrodynamics Response Experiment measurements. We conduct a magnetohydrodynamics simulation of the same event and show simulated ion temperatures, ion flows, and FACs that agree with the measurements. However, the observed plasma heating is less intense in the simulated results than in the TWINS and MMS data, indicating that some heating processes may be missing from the model. Plain Language Summary: Large chunks of energetic particles and enhanced magnetic field from the Sun can cause geomagnetic storms and substorms in the space surrounding Earth. During these active times, the energy from the Sun can get dumped into the nightside where ions and electrons are heated and propelled toward the Earth like from a slingshot. When these energetic particles get closer to the Earth, they can disrupt satellites and cause power outages, so scientists hope to improve our understanding and develop forecasting tools for these storms and substorms. Scientists have shown that the particles move toward the Earth in narrow channels. We demonstrate that these channels are heated and can be seen in temperature maps created from the NASA TWINS mission. To support our findings, we also compare the results to measurements from other satellites and computer simulations. This means that we can use such maps for more research and to improve forecasting models. For example, we found that the measured temperatures are higher than the simulated temperatures, indicating that more is needed in the models. We could also use a satellite like TWINS to act as a warning system for storms and substorms. Key Points: An interval of bursty flows during a magnetospheric substorm expansion phase is observed by Two Wide‐angle Imaging Neutral‐atom Spectrometers (TWINS), Magnetospheric MultiScale (MMS), and Active Magnetosphere and Planetary Electrodyamics Response Experiment and simulated using the Space Weather Modeling Framework The localized regions of ion heating observed by TWINS are directly related to the bursty plasma flow channel and substorm development The observed heating is less intense in the simulations than the TWINS and MMS data; additional heating processes are needed in the model